Games for adults? The place and role of games in the language teaching syllabus for adults - Kádár Blanka (2007)
In my thesis I write about the role and importance of language games in the methodology of teaching adults. My hypothesis is that games promote and help sustain a good atmosphere in language classes, thus making the whole teaching and learning process more enjoyable for both teachers and students. In the first part of the thesis facts that support the use of games in adult language teaching will be presented, while the second part will cover the classification of language games and their possible inclusion in the language teaching syllabus. In the third part the results of a survey on the application of language games in Hungarian (language) schools will be discussed, which was carried out in the form of questionnaires distributed to and filled in by learners and teachers of English. The primary aim of my thesis is not only to discover how games work in the adult language teaching process, but also to stress the importance of language games in adult language classes.